Zadarski Arbanasi - Babić, Dragutin (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2019)
The paper analyses the processes of assimilation and integration in the case study of the Arbanasi of Zadar. They came to Zadar and its surroundings in the mid-18th century from the area around the Skadar Lake in then Turkish Albania. In the 2014 empirical research in Zadar, 20 Arbanasi (12 women, 8 men), aged between 38 and 87, were interviewed. Through contacts with the local Croats and Italians their historical ethnic identity continuously dimished. Today a large majority of Arbanasi are declaring themselves as Croats and only a few of them as Italians, therefore they may be regarded as a subnational community. In the research (interviews), the Arbanasi were asked about the arrival of their ancestors to the region of Zadar and about the content of the community memory, which treasures what the Arbanasi collectively call the spirit of Arbanasihood.
Keywords: Arbanasi; asimilacija; identiteta; integracija; Zadar